Evaluation of abches and volumetric modulated arc therapy under deep inspiration breath-hold technique for patients with left-sided breast cancer: A retrospective observational study. Issue 39 (September 2019) - Yeh, Tien-Chi; Chi, Mau-Shin; Chi, Kwan-Hwa; Hsu, Chung-Hsien
Abstract : Abstract: Radiotherapy after breast-conserving surgery or mastectomy has clinical benefits including reducing local recurrence and improving overall survival. Deep inspiration breath-hold (DIBH) technique using the Abches system is an easy and practical method to reduce radiation dose to the heart and lungs. This retrospective study was proposed to investigate the dosimetric difference between Abches system and free breathing technique in treating left-sided breast cancer. Eligible patients underwent computed tomography (CT) scans to acquire both free breathing (FB) and DIBH technique data using the Abches. For each patient, both FB and DIBH image sets were planned based on the volumetric modulated arc therapy (VMAT). Radiation dose to the heart, ipsilateral lung, and contralateral lung was compared between the Abches system and FB. No significant differences in the planning target volume (PTV) (674.58 vs 665.88 cm 3, P = .29), mean dose (52.28 vs 52.03 Gy, P = .13), and volume received at the prescribed dose (Vpd) (94.66% vs 93.92%, P = .32) of PTV were observed between the FB and DIBH plans. Significant differences were found in mean heart (6.71 Gy vs 4.21 Gy, P < .001), heart V5 (22.73% vs 14.39%, P = .002), heart V20 (10.96% vs. 5.62%, P < .001), mean left lung (11.51 vs 10.07 Gy, P = .01), left lung V20 (22.88% vs 19.53%, P = .02), left lung V30 (18.58 vs 15.27%, P = .005), and mean right lung dose (.89 vs 72 Gy, P = .03). This is the first report on reduced mean left lung, mean right lung dose, and V20 of left lung using VMAT and Abches. The combination of Abches and VMAT can practically and efficiently reduce extraradiation doses to the heart and lungs.